1997
DOI: 10.1128/mcb.17.9.5410
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tyrosine Autophosphorylation Sites Negatively and Positively Modulate Neu-Mediated Transformation

Abstract: A number of cytoplasmic signaling molecules are thought to mediate mitogenic signaling from the activated Neu receptor tyrosine kinase through binding specific phosphotyrosine residues located within the intracellular portion of Neu/c-ErbB-2. An activated neu oncogene containing tyrosine-to-phenylalanine substitutions at each of the known autophosphorylation sites was generated and assessed for its specific transforming potential in Rat1 and NIH 3T3 fibroblasts. Mutation of these sites resulted in a dramatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
190
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(195 citation statements)
references
References 66 publications
3
190
1
1
Order By: Relevance
“…Copine-III does not possess an SH2-or a phosphotyrosine-pTyr binding domain. Shc has both domains and has also been found associated with pTyr1248 (Dankort et al, 1997;Schulze et al, 2005) (Figure 1). Shc was detected in Copine-III IPs from lysates of T47D cells, and Shc levels increased in response to HRG (Figure 5d).…”
Section: Tr Erbb2mentioning
confidence: 99%
See 1 more Smart Citation
“…Copine-III does not possess an SH2-or a phosphotyrosine-pTyr binding domain. Shc has both domains and has also been found associated with pTyr1248 (Dankort et al, 1997;Schulze et al, 2005) (Figure 1). Shc was detected in Copine-III IPs from lysates of T47D cells, and Shc levels increased in response to HRG (Figure 5d).…”
Section: Tr Erbb2mentioning
confidence: 99%
“…Tyr1028 couples to a pathway implicated in negative regulation of NeuT transforming potential, whereas the four other sites have a potentiating effect. Tyr1144, Tyr1201 and Tyr1227 signal through the Ras/Erk pathway by binding Grb2, Crk and Shc (Akiyama et al, 1991;Dankort et al, 1997Dankort et al, , 2001, which also binds Tyr1253 (Schulze et al, 2005). The role of pTyr residues has also been examined in migration assays.…”
Section: Introductionmentioning
confidence: 99%
“…Shc proteins are thought to promote Ras activation by indirectly recruiting Grb2 Rozakis-Adcock et al, 1992) through tyrosine phosphorylation of sites conforming to consensus Grb2 SH2 binding sites (Gotoh et al, 1997;Salcini et al, 1994;Songyang et al, 1994). Ras activity is required for e cient ErbB-2 (Ben- Levy et al, 1994;Dankort et al, 1997) and PyV-MT-(Jelinek and Hassell, 1992) mediated signaling.…”
Section: Ras Activationmentioning
confidence: 99%
“…While none of the Ā®ve known ErbB-2 tyrosine phosphorylation sites are required for transformation (Segatto et al, 1990;Mikami et al, 1992;Ben-Levy et al, 1994;Dankort et al, 1997), four sites (Y1144, Y1201, Y1226/7, Y1253) can independently mediate a transforming signal and require Ras activity to induce DNA synthesis (Dankort et al, 1997). Of these Y1144 and Y1226/7 respectively bind Grb2 and Shc and interaction directly correlates with transformation potential, thus providing a molecular mechanism for Ras activation (Dankort and Muller, unpublished observations).…”
Section: Ras Activationmentioning
confidence: 99%
“…A role for the mitogen activated protein kinases (MAPKs or Erks) in transformation by the ErbB2 receptor has been established by showing that overexpression of ErbB2 is associated with a considerably increased Erk/ MAP kinase activity in breast cancer cell lines (Janes et al, 1994). Furthermore, the autophosphorylation sites in the ErbB2/Neu receptor that allow coupling to Ras and the Erk/MAP kinase pathway appear to be very important for cell transformation (Ben-Levy et al, 1994;Dankort et al, 1997). The role of signal transduction pathways in transformation mediated by ligands of the EGF family is not well understood at present, but studies have shown that exogenously added EGF and heregulin/NDF can induce activation of the Erk/MAP kinases, Jnk/SAP kinases (stress activated protein kinases) and phosphatidyl inositol 3-kinase in mammary epithelial cell lines.…”
Section: Introductionmentioning
confidence: 99%